Kualitas Air dan Komunitas Zooplankton di Kawasan Segara Anakan Bagian Timur, Cilacap - Agatha Sih Piranti; Amalia Priska; Erwin Ardli Riyanto (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Water quality is a water condition that can be measured and tested based on certain parameters. Measurement of environtmental factors are divided into three, there are physical, chemistry, and biology. One of the the biological indicators which used to determine changes in water quality is zooplankton. Segara Anakan Cilacap waters has received input of solid material from industrial and residential waste, which made the water quality and its effect on zooplankton need to be studied. The purpose of this study is to determine the water quality of Segara Anakan, to find out the diversity and abundance of zooplankton in Segara Anakan, and also to know the relation between the water quality and the abundance of zooplankton. The result of the research found that over all the water quality in Segara Anakan Cilacap is still quiet good. The diversity of zooplankton is still relatively low to medium which is composed of 43 species of 8 orders. The abundance of zooplankton is around 175 - 1907 ind.l-1. The most abundant species is Laophonte brevirostris and Leptodiaptomus ashlandii. The relationship between the environmental factor and the abundance of zooplankton based on the regression analysis result found that the abundance equation = 3427 - 271 Salinitas + 0.74 TDS + 1090 BOD with R2 value is 0.863.